2019
DOI: 10.3390/polym11101604
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors for the Recycling of Different End-of-Life Materials: Wood Wastes, Automotive Shredded Residues, and Dismantled Wind Turbine Blades

Abstract: Different classes of wastes, namely wooden wastes, plastic fractions from automotive shredded residues, and glass fiber reinforced composite wastes obtained from dismantled wind turbines blades were analyzed in view of their possible recycling. Wooden wastes included municipal bulky wastes, construction and demolition wastes, and furniture wastes. The applied characterization protocol, based on Fourier transform infrared (FTIR) spectroscopy in attenuated total reflection (ATR) mode, scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The presented strategies focus on prolonging product lifetime and preserving resources, but do not explicitly account for safety issues involved with composite materials. Risks are found across the composite product life and include the release of volatile organic compounds, fibres and particles and dust [72,73]. All of these pose a threat to human health and the environment.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented strategies focus on prolonging product lifetime and preserving resources, but do not explicitly account for safety issues involved with composite materials. Risks are found across the composite product life and include the release of volatile organic compounds, fibres and particles and dust [72,73]. All of these pose a threat to human health and the environment.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…Zappeloni [73] discusses best practices to minimise such emissions in the manufacturing stage, and Medici expressed concerns over long-term outdoor exposure [74]. Additionally, (re)processing, which aims to separate, or at least downsize the materials, risks hazardous emissions [7,72,75]. Thus, next to preserving resources, additional measures are needed to address human, environmental and ecological impacts of manufacturing, using and reprocessing composite materials.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…Kim et al [10], in line with one of our previous works [11], show a thermal stabilization effect during the co-pyrolysis of waste automobile lubricating oil and polystyrene (i.e., degradation temperatures of the mixture shifted towards higher values, when compared to the pyrolysis of the pure compounds). A thermal stabilization effect of inorganic materials on the lignocellulose fraction in construction and demolition waste was also mentioned by Castaldo et al [12], and Avella et al [13] highlighted that compatibilizing agents induce a thermal stabilization of plastic and cellulose in composite material.…”
Section: Introductionmentioning
confidence: 79%
“…It has been reported that wood waste reprocessing for the production of new products is an economically viable plan (Carpio et al, 2013). Wood recycling is one of the basic steps towards a circular economy regenerative system that can able to minimize resource depletion and energy consumption (Keskisaari and Kärki, 2018;Castaldo et al, 2019). It also guaranteed the sustainability of the forest conservation in the emerging economies (Bergeron, 2014).…”
Section: Experiences In Wood Waste Management 21 International Expermentioning
confidence: 99%